The Consequences of Entrepreneurial Finance: Evidence from Angel Financings - Kerr, William R.; Lerner, Josh; Schoar, Antoinette (Review of Financial Studies, 2014)
This article documents the fact that ventures funded by two successful angel groups experience superior outcomes to rejected ventures: They have improved survival, exits, employment, patenting, Web traffic, and financing. We use strong discontinuities in angel- funding behavior over small changes in their collective interest levels to implement a regression discontinuity approach. We confirm the positive effects for venture operations, with qualitative support for a higher likelihood of successful exits. On the other hand, there is no difference in access to additional financing around the discontinuity. This might suggest that financing is not a central input of angel groups.